1966
DOI: 10.1037/h0023389
|View full text |Cite
|
Sign up to set email alerts
|

Social competence and psychiatric diagnosis.

Abstract: It was hypothesized that symptoms reflect a patient's social competence or maturity level and that this maturity level is related to the diagnosis he receives. Symptom scales based on empirical relations between symptoms and competence levels were constructed for 3 spheres of functioning: thought, affect, and action. Results obtained with 504 psychiatric patients showed that (a) placement on each symptom scale was significantly related to diagnosis; and (b) patients who could be rated on all 3 scales showed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Furthermore, nearly half of the psychologists originally contacted failed to respond, leaving us with a further restricted sample of unknown comparability to the original sample The two main dimensions identified, psychotic-neurotic and turning within oneselfturning to others, are not new to this study. Thus, the present results overlap with Eysenck's (1967) factor-analytically derived dimensions, with Phillips, Broverman, and Zigler's (1966) work on adaptation and symptom expression, and with Stone, Coles, Stinnet, and Sherman's (1971) multidimensional patient scaling. However, since these studies involved real-life patients, whereas the present study dealt with clinicians' stereotyped symptom orderings, as a consequence the present results are independent of actual symptom base rates.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, nearly half of the psychologists originally contacted failed to respond, leaving us with a further restricted sample of unknown comparability to the original sample The two main dimensions identified, psychotic-neurotic and turning within oneselfturning to others, are not new to this study. Thus, the present results overlap with Eysenck's (1967) factor-analytically derived dimensions, with Phillips, Broverman, and Zigler's (1966) work on adaptation and symptom expression, and with Stone, Coles, Stinnet, and Sherman's (1971) multidimensional patient scaling. However, since these studies involved real-life patients, whereas the present study dealt with clinicians' stereotyped symptom orderings, as a consequence the present results are independent of actual symptom base rates.…”
Section: Discussionsupporting
confidence: 63%
“…This article in conjunction with the authors' earlier findings that psychiatric diagnosis is related to attained level of social competence (Phillips, Broverman, & Zigler, 1966;Zigler & Phillips, 1961a) indicates that psychiatric diagnosis is essentially a complex indicator of at least three general dimensions of human behavior, namely, dominant mode of expression, social role, and general competence level. It should be noted that the findings of this and earlier studies have indicated that while these three general factors all share a certain amount of interrelationship, they are each somewhat independent of each other.…”
Section: Resultsmentioning
confidence: 51%
“…Unfortunately, the premorbid competence concept became a victim of its own success in the prediction of outcome in schizophrenia, with the work over the years confined to the repeated demonstration that premorbid competence is related to outcome, the development of a plethora of measures of premorbid competence, and repeated investigations of how the various measures of premorbid competence are related to one another. While some workers have employed the premorbid competence concept to explain variations in the symptom patterns displayed by schizophrenics (see Phillips, Broverman, & Zigler, 1966), the premorbid construct has generally not been used to illuminate other important issues in schizophrenia (e.g., treatment indicated and etiology). Gittelman- Klein and Klein (1969) wisely noted that in order to apply the premorbid competence construct more broadly, particularly in explaining the etiology of various subtypes of schizophrenia, one would have to expend much more theoretical effort than heretofore expended in coming to grips with the underlying conceptual dimensions assessed by premorbid adjustment scales.…”
Section: Theoretical Issuesmentioning
confidence: 99%